Development of Novel Vaccines Against PRRS Viruses in Pigs - Jantafong, Tippawan (Journal of Mahanakorn Veterinary Medicine, 2018)
Porcine reproductive and respiratory syndrome virus (PRRSV) is a causative agent of a devastating disease that namely Porcine Reproductive and Respiratory Syndrome (PRRS) brought huge losses to pork production in swine industry worldwide. The disease is characterized by massive reproductive failure and late term abortion in sows as well as respiratory disorder in piglets. In the present, PRRS is endemic in several countries in Asia such as China, Japan, South Korea, Taiwan and Thailand. As, PRRSV has become one of the most common viruses affecting swine population, several control strategies were established. However, these viruses still circulate and re-infection occurs in many swine herds. Of all control and prevention measures, vaccination is the main approach for control and eradication of PRRSV infection in swine herds since no specific treatment and no any antiviral drug is available for curing and control of PRRS. Thus, several studies have focused on the development of an effective vaccine against PRRSV in both experimental trials and field studies. Nevertheless, these vaccines still have several drawbacks. Thus, development of an effective PRRSV vaccine is one of the most interesting areas. This present review article provides the knowledge of recent novel PRRSV vaccine development. The information from this review article can be applied for further study about PRRSV vaccine development, resulting in enlighten veterinary practitioners and other related persons to develop more effective control measures aiming to PRRSV eradication.